Socio-Economic Sustainable Development of the Regions of Kazakhstan: Research of Demographic Potential - NAGIMA, Sagidolda; UMIRZAKOVNA, Rakhmetova Rakhilya; AMZEBEKOVNA, Musulmankulova Aigul; ABDRAHMANOVNA, Abenova Kulzada; АKMARAl, Kazykeshova (Journal of Environmental Management and Tourism, 2019)
The article deals with the problems of the demographic potential of the regions of Kazakhstan. Human resources are one of the most important factors in the socio-economic development of the country. During the period of establishing its independence, the Republic of Kazakhstan has undergone many reforms and crises. These changes had significantly influenced the demographic situation in the republic. Reproduction of the population in Kazakhstan is mainly characterized by a natural increase. However, in the 90s there was a large outflow of population to other countries due to the deterioration of the socio-economic situation. This situation has led to a demographic crisis, i.e. decrease in the birth rate, as well as to the uneven distribution of population by regions of the republic. The situation has improved since the beginning of 2000, starting in 2010, there has been a certain stability in the demographic situation, when the overall increase in the country was 1-2%. Given that this trend continues to this day, the question arises of which regions account for population growth and which regions are in the high-risk zone. As well as to identify the main factors that influence the demographic potential of the regions of Kazakhstan. The purpose of this study is to identify problems in the field of demography in the regions of Kazakhstan. The analysis was conducted on the data of the Statistics Committee of the Ministry of National Economy of the Republic of Kazakhstan. Initially, an analysis of structural shifts was carried out in population size by region, age structure of the republic’s population, the influence of the ethnic composition of regions on fertility was also considered, cluster analysis was used to divide regions by risk zones, as well as we considered the factors that affect fertility. An analysis of the results showed that regions with a predominate Kazakh and Turkic-speaking ethnic groups show a higher birth rate than regions where European ethnic groups are a majority; structural differences in population size and age composition become stronger with each period of differences; using cluster analysis, three zones were identified - a zone with low potential, which included eight regions, a medium-risk zone — we observe five regions, and a zone with high potential, which included three regions. Research hypothesis: the demographic potential of a country depends on the ethnic composition and socio-economic condition of the regions. The results of the study can be applied for research and analytical review. The research materials can be used in the development of regional development programs and the introduction of various approaches to the use of human resources and opportunities of each region.